Determinants of malaria spread among under-five children in Nigeria: results from a 2021 Nigerian malaria indicator cross-sectional survey - Isaac Isiko; Simon Nyegenye; Aaron Mwesigwa; Jackson Micheal Asingwire; Haron Olot; Shekina-Rhoda Chioma Amaka; Lenz Nwachinemere Okoro; Praise Amarachi Amaka Etane (BMC Pediatrics, 2024)
Abstract Background Malaria is a global disease burden, especially in Africa, with Nigeria having the highest prevalence of malaria, with approximately 50% affecting children. Children under five years of age are vulnerable to the risk of malaria spread. This research aimed to identify the determinants of malaria spread among children under the age of 5 in Nigeria. Methods This study used national malaria indicator survey data from 2021 (2021NMIS). The NMIS was implemented by the National Malaria Elimination Programme (NMEP), and data were collected between 12 October and 4 December 2021. This study included 3678 children, and data cleaning and analysis were performed via STATA version 17 software. Results There was a positive association between Child’s age in months of 13–23 (AOR = 2.97; 95% CI = 1.62–5.45), 24–35 months (AOR = 2.64; 95% CI = 1.43–4.88),36–47 months (AOR = 2.18; 95% CI = 1.17–4.08) and months of 48–59(AOR = 2.82; 95% CI = 1.53–5.23), households headed by females (AOR = 0.71; 95% CI = 0.54–0.95),households with all children slept in mosquito nets last night (AOR = 2.43; 95% CI = 1.39–4.21), some children slept in the mosquito bed net (AOR = 2.83; 95% CI = 1.50–5.35) and households with no mosquito bed nets (AOR = 2.18; 95% CI = 1.22–3.88),mothers who agreed to have heard or seen malaria messages in the last 6 months (AOR = 1.32; 95% CI = 1.62–1.74),respondents with medium level of awareness of malaria prevention messages had (AOR = 2.35; 95% CI = 1.62–3.4), Children from North East (AOR = 0.7; 95% CI = 0.54–0.9), South-South (AOR = 0.65; 95% CI = 0.5–0.85) and South West (AOR = 0.52; 95% CI = 0.37–0.73) and malaria status of children under five years of age in Nigeria. Conclusion The government and other concerned malaria prevention organizations should emphasize maternal education programs that are vital for malaria prevention, early symptom recognition, and timely treatment, empowering families to take proactive measures. Collaboration among health, education, and community organizations is also crucial for integrated malaria control and prevention.